The Effect of Poly(Methyl Methacrylate) on the Interfacial Interactions and Mechanical Properties of Plasticized Poly(Vinyl Chloride)/Poly(Lactic Acid) Blends - Astaneh, Reza Poorghasemi; Jahani, Yousef (Polymer engineering and science, 2025)
In this study, blends of plasticized PVC/PMMA/PLA were prepared in a twin‐screw extruder and their morphology, rheology, and mechanical performance are investigated. Thermodynamic work of adhesion suggested stronger interactions among PMMA and either PVC or PLA than PVC/PLA. Flory–Huggins interaction parameters implied high affinity of dioctyl phthalate (DOP) plasticizer to PMMA and PLA, and also a good tendency of PMMA to both PVC and PLA. SEM images proposed PMMA plasticization by DOP and miscibility between PVC and PMMA, which improved interfacial interactions. Formation of stress‐whitening paths during fracture proposed shear yielding fracture mechanism in ternary blends. Improved interfacial interactions were approved by complex viscosity variations. Flexural properties were enhanced by PMMA content. The blend containing 70% P‐PVC, 20% PLA, and 10% PMMA showed desired phase interactions with 57.6 kJ/m 2 impact strength, while 20% PMMA reversely decreased impact strength to 20.6 kJ/m 2 due to high DOP absorption and insufficient plasticization of other components. Blends with above 50 kJ/m 2 impact strength were found to be achievable at more than 22% DOP and less than 15% PMMA concentrations with respect to total amorphous fraction of blends.